INOVASI PRODUK OLAHAN: PEMBERDAYAAN MASYARAKAT MELALUI PELATIHAN KERUPUK NASI IKAN TONGKOL DI DESA MAITARA - Darmawaty, Darmawaty; Mutmainnah, Mutmainnah; Muksin, Darmiyati; Laela, Tri; Rumagia, Faizal; Kadir, Irwan Abdul (Jurnal Abdi Insani, 2025)
Maitara Village is a coastal area with abundant fisheries potential, especially tuna (Euthynnus affinis). However, its utilization is not optimal because it is still limited to fresh consumption and traditional processing, resulting in low economic value. On the other hand, household waste such as leftover rice is also still not optimally utilized. This is an opportunity in developing innovative food products based on local potential. This service activity aims to improve skills and community empowerment through training in making tuna rice crackers as an alternative to diversifying processed fisheries. The methods used include counseling, hands-on demonstration, and practice of product making by participants, who mostly consist of housewives, which was carried out on Maitara Island, Maitara Village, North Tidore Subdistrict, Tidore Islands City in July 2025. The results showed a significant increase in participants' knowledge and skills in processing local raw materials into valuable products. This activity also encourages changes in the mindset of the community about the importance of innovation, household waste management, and family economic empowerment. In conclusion, this training successfully provided an applicable and sustainable solution in developing local potential while reducing waste, as well as opening new entrepreneurial opportunities for the people of Maitara Village